Pewarisan Sifat Toleransi Padi Sawah (Oryza sativa L) Terhadap Cekaman Suhu Rendah - Yusuf L. Limbongan; Hajrial Aswidinnoor; Bambang S. Purwoko; , Trikoesoemaningtyas2 (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
One of the definite successful of rice breeding programs for increasing yield and tolerance to environmental stress condition is selection method. Selection method will be effectively if it is supported by a perfect knowledge of genetics character inheritance. The objectives of this study is to investigate the information of inheritance pattern adapted of rice towards low temperature stress condition. The experiment was conducted in both Sesean rural area, Toraja regency, South Sulawesi on 1500 m above sea levels, an mean temperature 15 o C, type of soil is Podzolic and at Bogor Agriculture Institute. This experiment is done in January 2006 until July 2007. The result showed that tolerance parental grew well and higher yield than sensitive parental. There were no significant differences between F1 and F1 reciprocal for all characters. Tolerance parental is more superior than sensitive parental in all characters have been tested. Mean of F1 generation is in between tolerance parental and sensitive parental. BCP1 has spheres wider than parentals and F1 generation, but BCP2 smaller than parentals and F1 generation. F2 generation is spheres wider than the average of both parentals. The m [d] [h] genetic model is the most suitable for all characters. Except, date of flowering and weight of filled rice where appropriate models is m [d] [h] [l]. Broad sense and narrow sense heritability is range between low to high. Based on the degree of dominant, additive effect is higher than dominant effect. The negative F value reached on date of flowering and fur lenght; and others characters, F value is positive.